Michael Katz's Contribution to Social and Social Welfare History. Issue 4 (2017) - Stern, Mark J.
Abstract : Michael Katz began work on social welfare during the late 1970s with a project entitled "The Casualties of Industrialization." That project led to a series of essays, Poverty and Policy in American History (Katz1983 ), and a few years later to In the Shadow of the Poorhouse (Katz1986 ). His reading in twentieth-century literature for Shadow —and the ideological and policy nostrums of the Reagan administration—allowed Katz to pivot to two books that frame contemporary welfare debates in their historical context— The Undeserving Poor in1989 and The Price of Citizenship in2001, as well as a set of essays Improving Poor People (Katz1995 ) that he published between the two.